Características de aceleração durante jogos oficiais de flag football - Pimentel Neto, José da Silva (2025)
External training loads have been used as a way of monitoring the stress caused by games and competitions, in this process inertial sensors such as accelerometers, gyroscopes and magnetometers are used in an integrated manner (inertial measurement units, IMU) to quantify actions such as quantities and levels of accelerations and impacts. Thus, the objective of this study was to investigate from the IMU, characteristics of sports actions quantified by these devices during official games in flag football. 40 male athletes (age 27.20 ± 4.03 years; mass 79.57 ± 11.94; height 1.76 ± 0.06) of 14 teams from all regions of the country (north [3], northeast [2], center-west [3], southeast [4], south [2]) were evaluated during the two competitions in Brazil, Attaching a device between the participants' scapula during a full match (among the first three matches of each team in the championship). the variables were filtered and stratified through custom routines in the "R" software. Comparisons were performed with software "GrapthPad Prism", between the game sectors (offense and defense) and game periods using t test, additionally cohen’s d effect size was used, moreover between the game positions (Rushers, defensive backs, quarterbacks and wide receivers) one way ANOVA. As results, no significant differences were found in the comparisons proposed in any variable between positions, sectors or game periods, but small effect size (Impz1 TE = 0.30; Impz3 TE = 0.37) was found in impact zones 1 (2 to 3 G) and 3 (4.5 to 6 G) between the first and second half. These findings suggest a linearity in acceleration demands between positions and sectors of game, however the drop in performance in game times can be relevant factors from the understanding load management in flag football as the players perform several games during the championships.